2019
DOI: 10.1128/jvi.00725-19
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Is Inhibited by a Noncanonical Antiviral Signaling Pathway Targeted by NS3-NS4A

Abstract: The hepatitis C virus (HCV) NS3-NS4A protease complex is required for viral replication and is the major viral innate immune evasion factor. NS3-NS4A evades antiviral innate immunity by inactivating several proteins, including MAVS, the signaling adaptor for RIG-I and MDA5, and Riplet, an E3 ubiquitin ligase that activates RIG-I. Here, we identified a Tyr-16-Phe (Y16F) change in the NS4A transmembrane domain that prevents NS3-NS4A targeting of Riplet but not MAVS. This Y16F substitution reduces HCV replication… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Of note, although several studies showed that Riplet modifies the CTD of RIG-I and thereby acts cooperatively with TRIM25 (refs [106][107][108] ), other studies suggested that Riplet can also modify the RIG-I CARDs 109,110 . Interestingly, Riplet has recently been implicated in an IRF3-mediated antiviral innate response that is independent of the RIG-I-MAVS signalling pathway 111 , which raises the question of whether the effect of Riplet deficiency on antiviral cytokine induction is primarily due to Riplet's role in RIG-I activation or its independent signalling function downstream of it. Finally, the ubiquitin ligases TRIM4 and Mex-3 RNA binding family member C (MEX3C) also reportedly promote RIG-I signal activation through K63-linked polyubiquitylation of multiple residues in the CARDs 112 , and thus a model of sequential and hierarchical RIG-I CARD ubiquitylation has been proposed 113 .…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
“…Of note, although several studies showed that Riplet modifies the CTD of RIG-I and thereby acts cooperatively with TRIM25 (refs [106][107][108] ), other studies suggested that Riplet can also modify the RIG-I CARDs 109,110 . Interestingly, Riplet has recently been implicated in an IRF3-mediated antiviral innate response that is independent of the RIG-I-MAVS signalling pathway 111 , which raises the question of whether the effect of Riplet deficiency on antiviral cytokine induction is primarily due to Riplet's role in RIG-I activation or its independent signalling function downstream of it. Finally, the ubiquitin ligases TRIM4 and Mex-3 RNA binding family member C (MEX3C) also reportedly promote RIG-I signal activation through K63-linked polyubiquitylation of multiple residues in the CARDs 112 , and thus a model of sequential and hierarchical RIG-I CARD ubiquitylation has been proposed 113 .…”
Section: Single-nucleotide Polymorphismsmentioning
confidence: 99%
“…In addition, there are several reports illustrating the RIG-I-independent antiviral activities of TRIM25 ( 32 , 33 ). On the other hand, it has been reported that Riplet can activates IRF3 transcription factor in a RIG-I-independent manner ( 34 ). Since there are differences in the experimental conditions between recent studies, and other possible explanations which have been recently discussed in more detail ( 35 ), the apparent contradictions should be reconciled by further studies.…”
Section: Ubiquitin Ligases That Mediate K63-linked Polyubiquitinationmentioning
confidence: 99%
“…Viral NS3-4A proteases cleaves viral poly-protein to produce mature viral proteins, and it also cleaves the MAVS adaptor, resulting in the release of MAVS from the mitochondrial outer membrane and thus inhibition of RIG-I-mediated type I IFN expression ( 10 ). The hepatitis C virus NS3-4A protein also binds to Riplet and inhibits Riplet-dependent antiviral activities ( 28 , 34 ). Although NS3-4A cleaves and degrade Riplet in a protease activity-dependent manner, it has bee also postulated that there is a RIG-I-independent Riplet antiviral activity, attenuated by NS3-4A, plays a role ( 28 , 34 ).…”
Section: Viral Proteins Targeting Ubiquitin Ligasesmentioning
confidence: 99%
“…More recently, Vazquez et al reported that the NS4A Y16F residue is responsible for Riplet inhibition but does not impair MAVS cleavage. They further discovered that inhibition of IRF3 activation and IFNs production, through the impairment of Riplet activity, was independent of the RIG-I/MAVS signaling pathway [63].…”
Section: Ns3-4amentioning
confidence: 99%
“…cleaves MAVS, to impair production of IFNs and proinflammatory cytokines [31,37,[52][53][54][55]57] cleaves TRIF, to impair production of IFNs and proinflammatory cytokines [28,58] inactivates Riplet, inhibiting RIG-I and IRF3 activation [62,63] binds to LUBAC, impairing the polyubiquitynation of NEMO required for NF-κB activation [66] induces degradation of STAT1, impairing the expression of antiviral effectors [67] binds to TBK1, impairing IRF3 activation [59][60][61] Core blocks NF-κB, to suppress inflammatory response [98,99] targets JAK/STAT pathway by targeting STAT1 and STAT2, inhibiting the production of ISGs [52,67,[104][105][106][107][108][110][111][112] E2 interacts with PKR, repressing its antiviral effects [89] NS5A interacts with PKR, repressing its antiviral effects [88,90] induces NAP1L1 degradation, inhibiting gene transcription essential for RIG-I-and TLR3-mediated responses [91] impedes RIG-I-and MDA5 activation, impairing IFNs expression [33] NS4B downregulates TRIF protein, inhibiting TLR3 signaling [68] interacts with STING, inhibiting the production of IFNs [69,70] p7 interacts with IFI16-16, inhibiting its antiviral function [114] Growing evidence demonstrates that HCV modifies host microRNA (miRNA) expression to modulate a diverse range of host functions [115]. It was re...…”
Section: N3-4amentioning
confidence: 99%